Ectopic Fasciola hepatica in lung of slaughtered cattle in the municipal abattoir of Cajamarca, Peru - Torrel Pajares, Teófilo Severino (2020)
The aim of this study was the evaluate the frequency and morphometric characterization of ectopic Fasciola hepatica in the lung. For this, 2066 lungs of cattle were evaluated in the municipal abattoir of Cajamarca, Peru, between July and August 2018. The lungs presenting macroscopic lesions were reviewed to determine the presence or absence of ectopic Fasciola hepatica. The frequency of erratic pulmonary fasciolosis was 3.68 ± 0.8%. Morphometrically, the ectopic Fasciola hepatica maintains a foliaceous shape, with pale pinkish to grey-brown coloration, measuring 10.36 ± 3.44 mm long and 4.31 ± 0.97 mm wide, and without evidence of oviposition.